THE EFFECTIVENESS OF LESSON STUDY MODEL IN THE STUDENTS' RESEARCH PROPOSAL WRITING - Marlina Bakri; Yuni Faryanti Sukri (Universitas Sembilanbelas November Kolaka, 2017)
This study aims to describe the effectiveness of the application of the lesson study model in the research proposals writing of the students of Indonesian Language and Literature Education Studies Program. In this research, there were two variables observed, namely variable X and Y. Variable X was lesson study as the independent variable, while variable Y was the students' ability to write research proposal as the dependent variable. The research design used in this research was one-group pretest-posttest design. The results showed that students who scored 75 and above were 38 people (95%) of the total sample of 40 students, while those who scored less than 75 were only 2 students (5%). Thus, it can be said that the level of students' ability to write a proposal has been sufficient if confirmed by the value of Kriteria Ketuntasan Minimal (KKM-Minimal Achievement Criterion), i.e. students were stted as success if they at least at the 85% get the score of 75 and above. Furthermore, based on the results of inferential analysis, obtained tcount value of 102.148 at the significant level p = 0,000, because p α = 0.05 or in other words tcount ttable (102.148 2.708) at sig. level of 0,000. Thus, the conclusion that can be obtained that the hypothesis was accepted. The result of the analysis showed that lesson study was effectively applied in learning writing research proposal of the fourth semester students of the Indonesian Language and Literature Education Study Program.